Formation in Leningrad of a System of Integrated Continuous Flow Management of Housing and Civil Construction: The Experience of the 70–80s of the Twentieth Century - N. V. Zakharova; A. V. Labudin (Управленческое консультирование)
The article deals with the problem of complex continuous flow management of the construction of a metropolis on the example of Leningrad of the late seventies and early eighties of the twentieth century and the proposed ways to solve it. Internal statistical data of the Leningrad City Executive Committee were used. The main problems in ensuring coordinated and systematic management of the construction complex in that historical period are analyzed. Conclusions are drawn about the relevance of this problem and methods of its solution in the conditions of a qualitatively new stage in the development of Russian society.